2022
DOI: 10.1093/brain/awac257
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effects of microglial activation on Alzheimer’s disease proteinopathy in older adults

Abstract: Women show disproportionate burden of Alzheimer’s disease (AD) pathology and higher AD dementia prevalences compared to men, yet the mechanisms driving these vulnerabilities are unknown. There is sexual dimorphism in immunologic functioning, and neuroimmune processes are implicated in AD genesis. Using neuropathology indicators from human brain tissue, we examined the mediational role of microglial activation on the relationship between amyloid and tau and how it differs by sex. 187 decedents (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 54 publications
4
29
0
Order By: Relevance
“…These findings support the view that earliest Aβ fibrillization induces an sTREM2‐related activation of microglia, which is in turn associated with p‐tau 181 increases, while sTREM2 increases may uncouple from Aβ severity at later stages. Our findings of microglial activation as a mediator of soluble p‐tau 181 increases is in line with a recent post‐mortem study in older adults showing that activated microglia partly mediated the relationship between Aβ and tau (Casaletto et al , 2022 ). In addition, several preclinical studies showed that activated microglia can enhance tau phosphorylation in animal models of AD and other tauopathies (Bhaskar et al , 2010 ; Lee et al , 2014 ; Maphis et al , 2015 ; Ising et al , 2019 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings support the view that earliest Aβ fibrillization induces an sTREM2‐related activation of microglia, which is in turn associated with p‐tau 181 increases, while sTREM2 increases may uncouple from Aβ severity at later stages. Our findings of microglial activation as a mediator of soluble p‐tau 181 increases is in line with a recent post‐mortem study in older adults showing that activated microglia partly mediated the relationship between Aβ and tau (Casaletto et al , 2022 ). In addition, several preclinical studies showed that activated microglia can enhance tau phosphorylation in animal models of AD and other tauopathies (Bhaskar et al , 2010 ; Lee et al , 2014 ; Maphis et al , 2015 ; Ising et al , 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, studies in sporadic AD patients found that a TREM2‐related microglial response is strongly correlated with soluble p‐tau but not with Aβ levels (Suárez‐Calvet et al , 2019 ) and that a TREM2‐related microglial response may promote the development of aggregated tau pathology in AD, as measured via tau‐PET (Vogels et al , 2019 ; Pascoal et al , 2021 ). Indeed, a recent post‐mortem study investigating the mediating effect of microglial activation on the Aβ to tau association in brain tissue revealed a mediation effect of 33% of microglia for the relationship between Aβ and tau (Casaletto et al , 2022 ). This suggests that microglial activation may be associated with tau hyperphosphorylation and therefore contribute to the development of tau pathology in AD.…”
Section: Introductionmentioning
confidence: 99%
“…These findings support the view that earliest Aβ fibrillization induces a sTREM2-related activation of microglia, which is in turn associated with p-tau increases, while sTREM2 increases may uncouple from Aβ severity at later stages. Our findings of microglial activation as a mediator of soluble p-tau increases is in line with a recent post mortem study in older adults showing that activated microglia partly mediated the relationship between Aβ and tau (15). In addition, several preclinical studies showed that activated microglia can enhance tau phosphorylation in animal models of AD and other tauopathies (11, 4244).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, studies in sporadic AD patients found that microglial activation is strongly correlated with fluid p-tau but not with Aβ levels (13) and that microglial activation may promote the development of aggregated tau pathology in AD, as measured via tau-PET (10, 14). Indeed, a recent post mortem study investigating the mediating effect of microglial activation on the Aβ to tau association in brain tissue revealed a mediation effect of 33% of microglia for the relationship between Aβ and tau (15). This suggests that microglial activation may be associated with tau hyperphosphorylation and therefore contribute to the development of tau pathology in AD.…”
Section: Introductionmentioning
confidence: 99%
“…We can therefore speculate on the possibility of sex-biased phenotypes within reactive astrocytes which have recently been placed in the center of AD pathology as an early event (i.e., reactive astrogliosis) in AD progression [91,92]. This would not be so surprising, since sex differences in glial cells have been previously described, reviewed elsewhere [93], and were recently also reported in microglial cells in AD [94].…”
Section: Alterations In Amino Acid Metabolism In Ad Are Sex-dependentmentioning
confidence: 65%